2021
DOI: 10.1039/d1ce01034d
|View full text |Cite
|
Sign up to set email alerts
|

Protein crystallisation with air bubble templates: case of gas–liquid–solid interfaces

Abstract: Crystal formation on air bubble–liquid interface, as soft template to efficiently prompt nucleation of proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…It was reported that the formation of needle-shaped crystals was due to the secondary nucleation and low supersaturation, which was consistent with the phenomena in this work; the needle-shaped crystals only appeared in stage 2 with existing crystals in the solution. However, in the hanging drop experiments with very low supersaturation, there were no needle-shaped crystals observed under similar crystallization conditions. The shear was reported to influence the crystallization process and crystal morphology, , and it was assumed that the shear also played an important role in the nucleation of the metastable needle-shaped crystal due to enhancement of mass transfer.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…It was reported that the formation of needle-shaped crystals was due to the secondary nucleation and low supersaturation, which was consistent with the phenomena in this work; the needle-shaped crystals only appeared in stage 2 with existing crystals in the solution. However, in the hanging drop experiments with very low supersaturation, there were no needle-shaped crystals observed under similar crystallization conditions. The shear was reported to influence the crystallization process and crystal morphology, , and it was assumed that the shear also played an important role in the nucleation of the metastable needle-shaped crystal due to enhancement of mass transfer.…”
Section: Resultsmentioning
confidence: 85%
“…The area, A (unit in μm 2 ), was measured by automatically calculating using the software to enclose the crystal edges in the images, which was then converted into crystal size. The crystal size was estimated by using the circular equivalent diameter, D (unit in μm), …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After mixing, the crystallisation solution had 0.55 M NaCl and 25–60 mg mL −1 lysozyme. The period between mixing and injecting into the microfluidic device was under 2 min, which was very short compared to the nucleation time at the equal crystallisation condition, 30 to ensure there was no nucleation before the mixed solution was pumped into the capillary. The liquid flowrate to the microfluidic chip was set at 60 ml h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…The globular protein like lysozyme was found to hold strong conformational stability and resisted the unfolding at the gas–liquid interface, 29 which can crystallise on the gas–liquid interface. 30 However, the mechanism of crystallisation on the interface between gas–liquid–solid are still not fully understood, the influences of the surface properties of the gas bubbles on protein molecules or the protein crystals require further investigations.…”
Section: Introductionmentioning
confidence: 99%